Breast Cancer Risk in Postmenopausal Women with Medical History of Thyroid Disorder in the Women's Health Initiative - Weng, Chien-Hsiang (Thyroid, 2020)
Background: The association between thyroid disorders and breast cancer remains controversial, in part, due to small cohort sizes and inconsistent findings. We investigated this association in postmenopausal women to determine whether hyper- or hypothyroidism is associated with the risk of developing breast cancer and to determine whether menopausal hormone therapy (MHT) further modifies the risk. Methods: We conducted a prospective cohort study of multiethnic U.S. postmenopausal women aged 50 to 79 years enrolled in both clinical trial and observational study arms between 1993 and 1998 and followed up through February 28, 2017. Development of invasive breast cancer after enrollment was recorded and a history of hyper- or hypothyroidism before the diagnosis of breast cancer was identified. The effect modification by MHT in both study arms was analyzed. All statistical tests were two sided. Results: Among a total of 134,122 women who were included in our study, 8137 participants developed invasive breast cancer during the follow-up period. There was a significant inverse association of invasive breast cancer among women with a history of hypothyroidism (hazard ratio [HR] 0.91, confidence interval [95% CI] 0.86–0.97) and among women who had taken levothyroxine [HR 0.89, 95% CI 0.82–0.96]. Evaluating effect modification by MHT use, the inverse association between hypothyroidism treated with thyroid replacement medications and breast cancer risk was strongest in non-MHT users [HR 0.80, 95% CI 0.69–0.93]. The results did not significantly differ by race/ethnicity. Although a history of hyperthyroidism was associated with an increased risk of invasive breast cancer [HR 1.11, 95% CI 0.91–1.35], this finding did not reach statistical significance. We did not see significant differences in the breast cancer Surveillance, Epidemiology, and End Results stages, histologic types, morphologic grades, or receptor status (estrogen receptor, progesterone receptor, human epidermal growth factor receptor 2) according to thyroid disorder status. Conclusions: Compared with women with no history of thyroid disorder, hypothyroidism was associated with a lower risk of breast cancer. This was mainly seen among those who received thyroid replacement therapy and had never used MHT. Among the treatment options for hypothyroidism, levothyroxine had the strongest inverse association with breast cancer risk.